Pengaruh enterprise risk management, profitabilitas, ukuran perusahaan, leverage, dan umur perusahaan terhadap nilai perusahaan perbankan yang terdaftar di BEI - Haryono, Alifian Aditya Lutfi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze enterprise risk management (ERM), profitability, firm size, leverage, and firm age on firm value. The analytical method used is multiple regression analysis with the help of SPSS 25 software with the classic assumption test results that meet the test requirements. The data used is secondary data derived from the annual reports of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study used purposive sampling in the selection of samples and the total sample used was 44 banks. The method applied is multiple regression analysis. The results found that profitability, firm size, leverage, and firm age had a positive impact on firm value. Meanwhile, ERM has no impact on firm value. From 180 companies in the banking sector in 2016-2020, it is shown that Enterprise risk management is not significant to firm value, as a result, hypothesis 1 is rejected. Profitability has a positive impact on firm value as a result, hypothesis two is accepted. Firm size has a positive impact on firm value as a result of which hypothesis three is accepted. Leverage has a positive impact on firm value as a result, hypothesis 4 is accepted. Firm age has a positive impact on firm value as a result, hypothesis 6 is accepted.